PENGARUH VIDEO PEMBELAJARAN TERHADAP ANTUSIASME SISWA KELAS X TKJ PADA MATA PELAJARAN SIMULASI DAN KOMUNIKASI DIGITAL DI SMK KHAMAS ASEMBAGUS - Kholiqin Kholiqin; Dyan Yuliana; Firman Jaya (PENDIDIKAN SAINS DAN TEKNOLOGI, 2022)
This study aims to determine whether or not there is an influence of learning videos on the enthusiasm of class X TKJ students in Simulation and Digital Communication subjects at Khamas Asembagus Vocational School. This study uses quantitative methods of observation, interviews, questionnaires and documentation. Based on data analysis using validity tests, reliability tests, normality tests, correlation coefficients and the results of the hypothesis (t-test) resulting in a questionnaire with 20 respondents, it is declared valid because Rcount > Rtable (0.444) and the residual value is normally distributed because the significance (0.200) > 0 ,05. Thus, learning videos are very influential with evidence at a high level of influence on student learning enthusiasm because they are able to provide motivation for students so that they do not feel bored and are not always monotonous in the teaching and learning process.